Chondrocalcinosis is common in the absence of knee involvement - Abhishek, Abishek; Doherty, Sally; Maciewicz, Rose; Muir, Kenneth; Zhang, Weiya; Doherty, Michael (BioMed Central Ltd, 2012)
Introduction: We aimed to describe the distribution of radiographic chondrocalcinosis (CC) and to examine whether metacarpophalangeal joint (MCPJ) calcification and CC at other joints occurs in the absence of knee involvement.